Nanoporous NiO/Ni(OH)2 plates incorporated with carbon nanotubes as active materials of rechargeable hybrid zinc batteries for improved energy efficiency and high-rate capability - Tan, P.; Chen, B.; Xu, H.; Cai, W.; Liu, M.; Shao, Zongping; Ni, M. (The Electrochemical Society, Inc, 2018)
© 2018 The Electrochemical Society. Although rechargeable zinc-air batteries are one of the promising power sources, the commercialization is hindered by a variety of technical hurdles, especially the low energy efficiency and poor rate capability due to the low discharge voltage. Herein, we report a high-performance composite composed of nanoporous NiO/Ni(OH)2 plates incorporated with carbon nanotubes. When used as the active material, unlike any single types of zinc-based batteries, the electrochemical reactions in both nickel-zinc and zinc-air batteries are combined. A high voltage of 1.7 V is obtained in the nickel-zinc battery region and a high capacity of over 800 mAh gZn-1 is demonstrated in the zinc-air battery region, attributed to the high pseudocapacitance and excellent activities of NiO/Ni(OH)2 nanoporous plates and the high electrical conductivity of carbon nanotubes. In addition, the battery can be cycled steadily for over 192 times at 5 mA cm-2 while maintaining the capacity at the energy efficiency of higher than 60%. Moreover, the discharge voltage profile and obtainable capacity remain unchanged even when the charge current density is increased by 8 times (from 2 to 16 mA cm-2), demonstrating excellent high-rate charge capability. The results shed light on further explorations of active materials for high-performance rechargeable hybrid batteries.